# How do you solve #3x-4=2x+8-5x#?

We can use terms from our right side combined to get

I hope this is useful.

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation 3x - 4 = 2x + 8 - 5x, you first combine like terms on both sides of the equation. Then, you isolate the variable x by performing the necessary operations to get it alone on one side of the equation.

Step 1: Combine like terms: 3x - 4 = 2x + 8 - 5x Combine the x terms on the right side: 3x - 4 = 2x - 5x + 8

Step 2: Combine like terms: 3x - 4 = -3x + 8 Add 3x to both sides to get all the x terms on one side: 3x + 3x - 4 = -3x + 3x + 8

Step 3: Simplify: 6x - 4 = 8 Add 4 to both sides to isolate the x term: 6x - 4 + 4 = 8 + 4

Step 4: Simplify: 6x = 12 Finally, divide both sides by 6 to solve for x: 6x/6 = 12/6

Step 5: Simplify: x = 2

So, the solution to the equation 3x - 4 = 2x + 8 - 5x is x = 2.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7